Study of Diagenesis and Pore Evolution of Triassic Jialingjiang Formation in Southern Puguang Gasfield - Qi Chen; Quan-wen Liu; Shenjian Wang (Journal of Chemistry)
The second member of Jialingjiang formation is considered to be an important gas reservoir with good exploration prospects in the southern Puguang gasfield. The diagenesis types are analyzed and different diagenetic stages are divided by analyzing carbon and oxygen isotopes as well as observing the slices. The widespread forms of diagenesis in the research area principally include compaction, cementation, pressure solution, dolomitization, recrystallization, dissolution, and tectonic disruption, among which cementation, dissolution, dolomitization, and recrystallization contribute greatly to the development of porosity in the reservoir. The reservoir has experienced four diagenetic stages: syndiagenetic stage, early stage of diagenesis, diagenetic stage, and late diagenetic stage. Most of the primary pores were destroyed in the diagenetic evolution stages of reservoir; the present porosity mainly belongs to the secondary pores.